2007
DOI: 10.1007/s00464-006-9122-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexamethasone, metoclopramide, and their combination in the prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy

Abstract: Dexamethasone and the combination of dexamethasone plus metoclopramide were more effective in preventing PONV than metoclopramide and placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 39 publications
3
46
1
4
Order By: Relevance
“…The current findings are identical to those reported by Nesek-Adam et al, the results demonstrated no variance in the occurrence of PONV during the study period (24 hours) between the groups who received Dexamethasone alone and combination. [22] The current results also are congruent to the study of Ivanov et al They found that the administration of Dexamethasone alone or in combination with Metoclopramide was more efficient in reducing PONV compared with Metoclopramide alone or without an antiemetic. [3] The most prevalent side effects reported in the current study were headache, tiredness, fatigue, drowsiness.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current findings are identical to those reported by Nesek-Adam et al, the results demonstrated no variance in the occurrence of PONV during the study period (24 hours) between the groups who received Dexamethasone alone and combination. [22] The current results also are congruent to the study of Ivanov et al They found that the administration of Dexamethasone alone or in combination with Metoclopramide was more efficient in reducing PONV compared with Metoclopramide alone or without an antiemetic. [3] The most prevalent side effects reported in the current study were headache, tiredness, fatigue, drowsiness.…”
Section: Discussionsupporting
confidence: 90%
“…[2,3,17,[20][21][22][23][24][25][26] Henzi et al analysed 17 studies comparing the efficacy of prophylactic Dexamethasone with a placebo for PONV, and found it more effective than placebo. [27] Conversely, Fujii et al conducted a study in women undergoing major gynaecological operations, and found that Dexamethasone at 8 mg dose alone did not reduce PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of new double-blind RCTs comparing dexamethasone with placebo controls corroborate findings reported in the original Guidelines indicating that this antiemetic is effective in the prophylaxis of postoperative vomiting and reduced use of rescue antiemetics, and for the prophylaxis of nausea when higher doses are administered (Category A1-B evidence). 8,12,24,26,29,36,37,39,41,43,44,[47][48][49][50][51][52][53][54][55][56] The consultants and ASA members agree that the pharmacologic prophylaxis of nausea and vomiting improves patient comfort and satisfaction, reduces time to discharge, and should be done selectively. Multiple Pharmacologic Agents for Prophylaxis of Nausea and Vomiting.…”
Section: A1-e Evidence)mentioning
confidence: 99%
“…PONV can lead to sweating, tachycardia, abdominal pain, prolonged recovery duration and increased risk of aspiration (3). The etiology of PONV is not still known well, but it is probably a multifactorial phenomenon (4,5). Gas entrance into the abdominal cavity during laparoscopy can cause increased pressure of peritoneal cavity which may lead to PONV (3).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged entrance of CO 2 leads to pneumo peritoneum, peritoneal distention and diaphragmatic stimulation. Intra-abdominal manipulation is one of the causes of PONV (4,5). Different medications have been evaluated in PONV prophylaxis and patient satisfaction after cholecystectomy (1-7).…”
Section: Introductionmentioning
confidence: 99%